Responsibility and Ethico-moral Values in Counselling and Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2005)
This paper reviews notions of responsibility relating to the provision of counselling and psychotherapy. The British Association for Counselling and Psychotherapy Ethical Framework for Good Practice in Counselling and Psychotherapy (2002) speaks of ethics that should consider 'values', 'principles' and 'personal qualities', and that 'principles direct attention to important ethical responsibilities'; but in what way are these constituted as a responsibility in the therapeutic encounter, and how or why are they framed as ethics or morality? It is argued that responsibility infers an 'other' to whom one is responsible. In so far as responsibility is a formulation of value, it is circumscribed by considerations of ethics, morality and power, all of which can impinge on the therapeutic encounter. It is therefore important to trace the development of these elements as we practice them in the therapeutic encounter.